Development and Erosion of Folk Dances among Magars in Syangja District - Sinjali, Bishnu Kumar (Journal of Nepalese Studies, 2025)
The area of confluence of the Aandi and the Kali Gandaki Rivers of Syangja has been the habitat of Magars from time immemorial. This research was carried out in these nine VDCs of Syangja district in 2015, through the qualitative method. During the 1960s, the Siddartha highway crossed the district, and after the policy of ‘aphno gau aphai banau’ by the government of Nepal, village roads were constructed touching all the villages of Magar settlements. Similarly, there were two hydropower stations, providing electricity in every village. The schools and colleges from both the government and private sectors mushroomed, and the media, such as FM radios and TV cables, also reached into Magar society. But, the cables, But the traditional songs and dances such as Sorathi (Karhaang-Naach), Ghāntu, and Rodi-culture But the Rodi culture, and so on, were found rusting. The new generations were found forgetting them. Rarely has such a culture had traditional and cultural events conducted these days. In the development process, there was low priority given to IPIA, SIA, the development of SIA, and IPP from the development agency, SIA, and Magars were found unaware about it. Therefore, such heritages of Nepal are eroding and dying. If such intangible heritages die, it will be costly to make them revive. The folk dances and songs of Magars are endangered heritages that will die, an endangered situation in the district due to unplanned development.